From DIY Avant-gardism to Icons of German New Wave: Einstürzende Neubauten and the Legacy of “Ingenious Dilletants” - Kuchar, Robin (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
Originating from the avant-gardist part of Berlin’s “ingenious dilletants” of the late 1970s and early 1980s, Einstürzende Neubauten have been playing a significant role in Western popular culture for more than 40 years. This article investigates Einstürzende Neubauten’s reception and legacy-building process by using ethnographic field research and documentary analysis. The analysis focuses the dimensions of musical traditions and innovations within the Neue Deutsche Welle (German New Wave) movement, the artistic and philosophic approach of the “dilletants” as well as the social and local context of Berlin during the times of Cold War.
Keywords: New Wave; Neue Deutsche Welle; Ingenious Dilletants; Avantgarde; DIY; Berlin